2013
DOI: 10.1177/1045389x13494934
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a magnetorheological energy absorber design analysis

Abstract: A key challenge when designing linear stroke magnetorheological energy absorbers for high-speed impact is that high piston speeds in linear stroke magnetorheological energy absorbers induce high Reynolds number flows in the magnetic valve of the magnetorheological energy absorber, so that achieving high controllable dynamic range can be a design challenge. So far, the research on magnetorheological energy absorbers has typically assumed that the off-state force increases linearly with piston velocity. But at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 24 publications
0
51
0
1
Order By: Relevance
“…But, in order to compare, here we assume the stroke of the conventional MREA is the same with the MREA with an internal bypass, as shown in figure 4. [1,17]. To have an idential yield damping force of the MREAs, the damping forces of the two MREAs is very different.…”
Section: Comparison Of Mreasmentioning
confidence: 98%
See 1 more Smart Citation
“…But, in order to compare, here we assume the stroke of the conventional MREA is the same with the MREA with an internal bypass, as shown in figure 4. [1,17]. To have an idential yield damping force of the MREAs, the damping forces of the two MREAs is very different.…”
Section: Comparison Of Mreasmentioning
confidence: 98%
“…Magnetorheological energy absorbers (MREAs), based on MR fluids, have an excellent controllable damping performance as a semi-active actuator, and would be one of the most promising actuators for shock and vibration control systems [1]. In the past decades, MREAs have been widely applied to and investigated in shock and vibration control systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the damper with shims added to the valve of the complex shape, and at high volumetric flow rates, due to the short length of the passages, the minor losses are significant and nonnegligible relative to viscous loss [15]. Wereley et al indicated that for the MR damper without shims, it is necessary to take minor losses into account for predicting the damping force at high piston velocity (>1 m/s) when the MR damper is subjected to intense impacts, such as aircraft landing gear, crashworthy helicopter seat suspension systems, mine blast seat suspension systems, and gun recoil systems [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As most of research involving analytical models for predicting damper stroking load have focused on vibration isolation problems, where piston velocities remain low (≤1 m/s), these models typically neglect the minor losses [15,[21][22][23]. According to the study by Sohn et al, for the MR damper that was subjected to piston velocity lower than 1 m/s and without shims in piston of the simple shape, it may also be necessary to take the minor losses into account for the analytical model of the MR damper.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, MR dampers have been employed as vibration mitigation devices for a number of applications, such as seismic dampers [1][2][3][4][5][6][7], seat dampers [8][9][10][11], and vibration isolators [12][13][14][15][16]. More recently, MR dampers have been also applied to aerial and ground vehicles as crashworthiness devices, such as landing gear oleos [17][18][19][20], impact dampers [21][22][23][24][25][26], and energy absorbers [27][28][29].…”
Section: Introductionmentioning
confidence: 99%